PERTANGGUNGJAWABAN ATAS PRIORITAS PENGGUNAAN DANA DESA DI DAERAH TERTINGGAL DITENGAH PANDEMI COVID 19 - Ro’is Alfauzi (DIKTUM: Jurnal Syariah dan Hukum, 2020)
Abstract: village communities in improving the development aspects, and empowering communities in the village. During the outbreak of the COVID 19 virus pandemic, the village minister has a concept of the latest regulation, namely Permendes (village minister regulation) Development of Disadvantaged Areas and Transmigration Number 6 of 2020 concerning Amendments to the Regulation of the Village Minister for Disadvantaged Areas and Transmigration Number 11 of 2019 concerning Priority for the Use of Village Funds in 2020 it specifically contains the allocation of village funds as handling of the COVID 19 pandemic and other non-natural disasters, especially in underdeveloped areas or underdeveloped villages, so that the village government in allocating funds can be directly monitored by the community from the level of responsibility and the point of view of its authority.